ANALISIS SOSIOLOGI HUKUM TERHADAP BELUM DIRATIFIKASIKANNYA KONVENSI CISG OLEH INDONESIA DITINJAU DARI PERSPEKTIF TEORI SISTEM HUKUM - Mahmud Haidir Harahap; Rosmalinda; Agusmidah; Rosmalinda Rosmalinda; Agusmidah Agusmidah (Bajang Institute, 2026)
This study examines Indonesia's non-ratification of the United Nations Convention on Contracts for the International Sale of Goods (CISG) from the perspective of Lawrence M. Friedman's Legal System Theory, which emphasizes three main elements: structure, substance, and legal culture. The purpose of this study is to analyze the integration of these three factors and to identify the legal, administrative, and social obstacles that hinder the ratification of the CISG. The method used is a qualitative approach with a socio-legal research type through literature studies and interviews with academics and practitioners of international trade law. The results of the study indicate that the non-ratification of the CISG is influenced by three main factors. First, structurally, coordination between government agencies involved in the ratification process is still weak and not yet integrated. Second, in terms of legal substance, there are differences in principles and norms between the CISG and national civil law that raise concerns about disharmony. Third, the legal culture of policymakers and business actors who are still conservative towards international law slows down the acceptance of this convention. In addition, administrative obstacles such as lengthy bureaucracy, lack of human resource capacity, and the perception that CISG ratification is not urgent also contribute to inhibiting factors. This study concludes that the lack of integration between the structure, substance, and legal culture is the main root of the failure to ratify the CISG in Indonesia. Therefore, legal system reform is needed through strengthening institutional coordination, harmonizing the substance of contract law, and increasing literacy and awareness of international law among policymakers and business actors.